Stress and emotional wellbeing of parents due to change in routine for children with Autism Spectrum Disorder (ASD) at home during COVID-19 pandemic in Saudi Arabia - Alhuzimi, Talal (Research in developmental disabilities, 2021)
•Parental stress and emotional well-being were impacted by frequency and usefulness of ASD support received during pandemic.•The study found that parental stress and emotional well-being of parents in Saudi Arabia had been impacted by the pandemic.•This study recommends the involvement of Ministry of Health to establish support services for parents of children with ASD. Parents of children with Autism Spectrum Disorder (ASD) experience considerable amounts of stress and impaired emotional well-being. Consequently, it is likely that these have been adversely impacted by COVID-19 outbreak due to disruptions to the schedules of children with ASD. This study investigated the stress and emotional well-being of parents of children with ASD in Saudi Arabia during the COVID-19 pandemic. The study obtained quantitative data from 150 parents of children with ASD from different regions in Saudi Arabia using an online survey. The data collected included demographic data of the parents, ASD status of the family, ASD support during COVID-19 pandemic, severity of ASD behaviours in comparison to the pre- COVID-19 status eating behaviour of the child with ASD, Parental Stress, and emotional well-being. The PSI-short form (PSI-SF) (Abidin, 1995) scale was utilised to obtain data related to parental stress and the General Health Questionnaire (GHQ-12) (Goldberg, 1992) scale was utilised to obtain data related to parents’ emotional well-being. The study found that family ASD status (in particular, age and gender of child with ASD, and severity of his/her symptoms) had a significant impact on parental stress and emotional well-being. Moreover, parental stress and emotional well-being were negatively impacted by the frequency and usefulness of ASD support received during COVID-19 pandemic. These were also adversely impacted by the change in severity of ASD behaviours of the children with ASD. Finally, parental stress was found to have a negative impact on the emotional well-being of parents. Overall, the study found that the parental stress and emotional well-being of parents of children with ASD in Saudi Arabia had been unfavourably impacted by COVID-19 pandemic. Overall, the study found that the parental stress and emotional well-being of parents with ASD in Saudi Arabia had been unfavourably impacted by COVID-19 pandemic. This study recommends the involvement of the Saudi Ministry of Health to establish and extend support services to support parents of children with ASD. Moreover, the provision of training programs to help parents deal with the characteristic behaviour of their children with ASD such as, the ability to maintain routines, aggressive or repetitive behaviour, is also recommended.